The Role of Principal's Leadership and Learning Organization to Improve Teacher’s Leadership - Rais Hidayat; Yuyun Elizabeth Patras (AL-ISHLAH: Jurnal Pendidikan, 2023)
Learning can work well when teacher leadership plays an optimal role. This study aims to improve teacher leadership through the influence of principal leadership and learning organizations. Quantitative methods were used in this research. The participants of this study were 1200 Indonesian teachers. The data was obtained through the questionnaire instrument. Data analysis uses the analysis path through SMART PLS. The research found that principal leadership and learning organizations can improve teacher leadership. Strategies to improve teacher leadership through the principal's leadership and learning organization are carried out by improving these variable indicators, including being a main motivator of learning, implementing school vision, doing quality assurance of learning, dialogue with various new ideas, and doing school development. Based on these findings, education stakeholders can discuss and promote teacher leadership competency improvements.